Does the Community College Pathway Influence the Selectivity of Students' Destination 4-Year Institution?. (October 2019) - Ortagus, Justin C.; Hu, Xiaodan
Objectives: In this study, we explore the influence of enrolling initially at a community college before transferring to a 4-year institution on the selectivity of the destination 4-year institution.Method: We leverage nationally representative data and a propensity score matching approach to compare the institutional selectivity between students who begin at a community college before transferring to a 4-year institution and those who begin at a 4-year college or university. To estimate the relationship between the community college pathway and institutional selectivity, we employ an ordinal logistic regression model.Results: We find that transferring from a community college to a 4-year institution had a positive influence on the selectivity of students' destination 4-year institution. More specifically, students who enroll initially at a community college before transferring to a 4-year institution have a greater probability of attending a very selective 4-year institution and moderately selective 4-year institution when compared with native 4-year students. Students who transferred from a community college have a lower probability of attending minimally selective 4-year institutions and open-admission 4-year institutions when compared with otherwise-similar students who began at a 4-year institution.Contributions: By showing a positive relationship between the vertical transfer and the level of selectivity of students' destination 4-year institution, this study highlights a potential benefit of beginning at a community college before transferring to a 4-year institution.